Priorities Media Richness of Users of Iraqi Electronic Newspapers - Hassan, Saad Kadhim (ALBAHITH ALALAMI, 2016)
The electronic press is one of the distinctive media due to its unique features such as instant publishing and interactivity, uses multimedia, the use of hypertext, the personalization of media content, getting echo of the media messages provision of electronic archive of previous numbers of the newspaper. The richness theory means that media are different depending on its wealth aspects which distinguish it from other media. The aspects of wealth here represent the features that characterize online press and constitute factors of media richness. The researcher studies the properties of Iraqi media richness of their users. The researcher uses a field study to get the goals of the research and tests the hypotheses of media richness theory.